Symposium 13: The Role of Participatory Evaluation in democratising Education Processes in the Public Administration: Experiences from the Tuscany region - Molinari, Francesco (Proceedings of the International Conference on Networked Learning, 2008)
Almost forty years ago, Peter Drucker, the famous ’guru’ of management, advocated the building up of "an independent agency ...independent of pressures from the executive as well as from the legislature" to play the role of ’performance auditor’ for Public Administrations, that is, to convert people’s expectations into policy goals and to compare with them the results obtained. At the other extreme lie Robert Dahl’s conditions for democratic decision making (i.e. Effective participation, Equality in voting, Gaining enlightened understanding, Exercising final control over the agenda, Inclusion of all adults), each of them raising sensitive and unsolved issues in the area of political access, equality and legitimisation. For instance, it is known from Sherry Arnstein’s seminal work that the development of participation in a selected context can reach different levels of granularity, including ’loose coupling’ and rhetoric "manipulation". Moreover, Dahl himself admits that in the real world, it is very unlikely that every citizen can have equal opportunities to influence the policy agenda. As James Fishkin clearly stated: "The (real) problem of democratic reform is ... how to bring people into the process under conditions where they can be engaged to think seriously and fully about public issues". However, this can be simply impossible to reach as the number of participants in public debates increases above a certain, very low threshold. Again it was Robert Dahl to show this paradox with a back-of-the-envelope calculation: "if an association were to make one decision a day, allow ten hours a day for discussion, and permit each member just ten minutes - rather extreme assumptions - then the association could not have more than sixty members" in order to allow everyone to have their say. While Drucker’s idea of an agency has not taken place so far, modern regulation theories now admit in its place the establishment of rules, procedures and standards, helping to make the Governments more accountable for their performance towards the citizens. Some international comparisons (from OECD Puma to EU Sigma) already show that the ’power of standards’ can be used to elicit process reengineering, comparability and harmonisation of practices in tge Public Administration. However, an insufficient attention has been given until now to change realised through quality management principles implementation. More generally, we believe that a unified and systematic approach to public performance evaluation is missing, which should make use of innovative concepts and tools like social and democratic dialogue and an extensive participation of citizens/customers in the governance and accountability process. The Living Labs concept is a recent innovation approach set forth in Northern Europe, through which all stakeholders of a product, service or application actively participate in its development process. Stakeholders can be public authorities, civic communities, SMEs and large industries, academia, content providers etc. The underlying R&D methodology enables innovation to be created and validated in a collaborative, multi-context, real-life environment, where the person is focused and monitored in all his/her social roles as (e.g.) a citizen, user, consumer or worker. This human-centric, experience-based perspective does not only ensure a user-driven design and development of products, services or applications, but also user acceptance. The idea is to reach a more sustainable innovation by taking benefit of the ideas, experiences and knowledge of the people involved with respect to their daily needs, in their every day lives, encompassing all their societal roles. Additional methodology reflections are needed to assess whether the Living Labs paradigm can be helpful in reviving and consolidating the theoretical foundations for a citizens-focused, participatory performance measurement system that is more coherent with the increasingly ’networked’ configuration of modern Public Administration and the need to find a balanced pathway between budget restrictions and quality assessment of ’government reengineering processes’.